EPIDEMIOLOGICAL SURVEY OF TRICHOMONAS VAGINALIS AMONG YEAR 5 STUDENTS TAKING PARASITOLOGY AT THE FEDERAL UNIVERSITY OF TECHNOLOGY, MINNA, NIGER STATE, NIGERIA - EKE, SAMUEL SUNDAY; NWOKOCHA, FAVOUR AMARACHI; KT, MUMUNEY; YAMMAN, HADIJAH USMAN; ONOJAFE, JOSEPH O; AGHA, CHIDIEBERE; UDEH, EMMANUEL OCHIGBO; OKPOKO, VALENTINE OBINNA (Innovare Journal of Medical Sciences, 2021)
Aim and Objective: The aim of this study was to see how popular Trichomonas vaginalis was among year 5 parasitology students at the Federal University of Technology in Minna, Niger State. Methods: A total of 239 high vaginal swabs and urine specimens were collected aseptically from male and female students, respectively, using a sterile swab stick and clean containers, for the evaluation of T. vaginalis occurrence under the microscope. Results: A total of 96 (40.17%) of the 239 students examined were found to have T. vaginalis infection, with female students having the highest prevalence 67 (50.0%), and male students having the lowest prevalence 29 (27.62%). The department of biology education had the most infections with 25 (41.67%), followed by the department of biology with 41 (41.41%), and the department of microbiology with 30 (37.50%). The highest infection rate was 34 (50.75%) in the age group of 21–25 years, followed by 17 (44.74%) in the age group of 31–35 years, and 5 (25.0%) in the age group of 46–50 years. There was no statistically significant difference in infection rates depending on age of the students. Conclusion: Vaginal trichomoniasis is very common among female students in year 5 at the Federal University of Technology in Minna, and it often goes unnoticed.